Philippine English in education and workplace: An integrative review of its roles - Junar Marquez (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
Despite the growing prominence of Philippine English (PhE) due to its local and global demands, there is an observed lack of integrative syntheses that specify its roles in education and the workplace through a conceptual representation. With the guidance of Spolsky’s (2008) language policy framework, this descriptive qualitative research employed a thematic synthesis to review related studies aimed at synthesizing and enumerating the roles of PhE in education and the workplace, which led to the development of a conceptual framework. The paper included 15 related studies published in peer-reviewed journals between 2021 and 2025. The analysis identified multiple roles of PhE in education, including its association with socio-economic mobility, pedagogical practices, language anxiety, instructional use, and identity construction. On the other hand, the roles of PhE in the workplace include PhE's global economic advantage, inferiority, and limited utilization. Moreover, it is concluded that the roles of PhE may vary depending on the language ideologies at both the macro and micro levels of Philippine society. Specifically, these have implications for the language policies and practices implemented at the meso (education and workplace) level of the Philippine society. Finally, it is recommended that a systematic literature review with a wider set of search engines beyond Google Scholar and a larger number of related studies focusing on the governing language ideologies toward PhE be analyzed to further confirm the results presented in this study.